Laparoscopic fundoplication for a child with abdominal intrathecal Baclofen pump. Issue 3 (20th August 2019) - Okata, Yuichi; Bitoh, Yuko; Aida, Yosuke; Miyauchi, Harunori; Nakatani, Taichi; Tomioka, Yuichiro
Abstract: This is the first case report describing a laparoscopic fundoplication in a child with an intrathecal Baclofen pump which was inserted because of severe spasticity secondary to cerebral palsy. The child had symptoms of gastroesophageal reflux with recurrent episodes of aspiration pneumonia. These were managed with a gastrostomy and conservative therapy with no success. The presence of an intrathecal Baclofen pump makes abdominal surgery challenging and carries the risk of pump infection with its associated sequelae. However, we performed a successful laparoscopic fundoplication with no intraoperative complications and the child was asymptomatic at 18 months follow‐up.